Brain Diffusivity and Structural Changes in the R6/2 Mouse Model of Huntington Disease. Issue 7 (11th October 2016) - Vorisek, Ivan; Syka, Michael; Vargova, Lydia
Abstract : Diffusion‐weighted magnetic resonance (DW‐MR) is an important diagnostic tool in Huntington disease (HD), a fatal hereditary neurodegenerative disorder. To clarify the nature of diffusivity changes in HD, we compared the apparent diffusion coefficient of water (ADCW ) acquired by DW‐MR with extracellular space volume fraction α and tortuosity λ, measured by the iontophoretic method in the R6/2 mouse model of HD and in wild‐type controls (WT). In anisotropic globus pallidus (GP), diffusion measurements were performed in the mediolateral ( x ), rostrocaudal ( y ), and ventrodorsal ( z ) axes. In HD animals, we detected an increase in ADCW in all axes and larger α than in WT mice. No significant difference between WT and HD mice was found in the values of tortuosity (λx, λy, λz ). Despite structural changes in GP, diffusion anisotropy was unaffected in HD mice. Immunohistochemical analysis revealed in HD mice weaker expression of extracellular matrix and a decrease in neuron numbers compared with WT mice. Glial fibrillary acidic protein staining detected astrogliosis‐like changes in the morphology of astrocytic processes in HD GP. In the somatosensory cortex, no significant differences in the studied parameters were found. We conclude that in the R6/2 model of HD, a decrease in the number of neurons in the GP results in increased ADCW and α values. Values of λ were not significantly changed as the increase of diffusion obstacles formed by reactive astrocytes was compensated for by the extracellular matrix reduction. © 2016 Wiley Periodicals, Inc. Abstract : Degenerative tissue changes in the globus pallidus (GP) of R6/2 mouse model of Huntington disease include extracellular matrix reduction, loss of neurons, and astrocytic rebuilding. These alterations result in a decrease of apparent diffusion coefficient of water associated with the enlargement of the extracellular space with the maintenance of an anisotropic diffusion.